KEGIATAN EKSTRAKURIKULER HEIKING SEBAGAI GERAKAN MITIGASI BENCANA OLEH SISWA MADRASAH TSANAWIYAH NEGERI (MTSN) 2 AGAM - Salim, Agus; Hanani, Silfia; Sesmiarni, Zulfani; Yaldi, Yusri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Hiking activities are one form of extracurricular activities in Scouting activities carried out by students of Madrasah Tsanawiyah Negeri (MTsN) 2 Agam as part of the disaster mitigation movement. This abstract presents the results of research on the significance of Scout activities in the form of hiking in the perspective of disaster mitigation in the Madrasah. The research was conducted through direct observation, interviews, and analysis of related documents. The results showed that hiking activities are not only a means of recreation, but also have a significant impact in disaster preparation and mitigation in the Madrasah environment. Through this activity, students are trained to be more responsive to the surrounding environment, develop survival skills, and understand the importance of safety in emergency conditions. In addition, hiking activities are also a means to increase awareness of the natural environment, strengthen a sense of solidarity between students, and build togetherness in facing potential disasters. Thus, hiking activities at MTsN 2 Agam are not only a forum for student character building, but also an integral part of the disaster mitigation strategy in Madrasah. In conclusion, the Scout hiking activities of MTsN 2 Agam students can be considered as part of an effective disaster mitigation movement, as it makes a significant contribution in preparation, response, and recovery from disasters. Therefore, it is recommended that the hiking activities of.